Inter-Satellite Cooperative Computing Scheme Driven by Business Graph in LEO Satellite Network - Xiaobo GUO; Zhiyuan REN; Wenchi CHENG; Zhe JI (天地一体化信息网络)
Low earth orbit-satellite network (LEO-SN) has the advantages of wide coverage and short satellite-to-earth link, and has become a current hot research fi eld.A business graph-driven inter-satellite collaborative computing method in LEO-SN was proposed to solve the problem of high transmission delay when the task was oﬄ oaded to the cloud computing center.This method shielded the dynamics of LEO-SN by relying on the weighted time expansion graph model, combined multiple satellite computing resources, and dispatches tasks in the form of a directed acyclic graph to the satellites in the transmission path, thereby realizing the ＆quot;computing while transmitting” of user services in the satellite cluster.The simulation results showed that when the data volume was 5 MB, the latency performance of on-orbit collaborative computing was improved by 58.9% compared to ground cloud computing.